Impact of mobile context-aware applications on human computer interaction - Chamasemani, Fereshteh Falah; Affendey, Lilly Suriani (Asian Research Publication Network, 2014)
The rapid growth of technological advances and availability of mobile devices has raised the opportunity to innovate feasible context-aware applications with the ability to access information anywhere and anytime. Therefore, this paper intends to review the recent developed mobile context-aware application. The reviewed articles are selected based on their application domains which cover the following six categories: smart space, healthcare, advertising, mobile guide, memory aid and disaster alerting applications. The selected applications are discussed based on their designed techniques, simulations and areas to show their impact on human computer interaction.